A sensitive radioimmunoprecipitation assay for assessing the clinical relevance of antibodies to IFN β. Issue 9 (21st August 2003) - Lawrence, N; Oger, J; Aziz, T; Palace, J; Vincent, A
Abstract : Background: Some multiple sclerosis (MS) patients treated with interferon beta (IFN β) develop antibodies to the drug. Neutralising antibody (NAB) assays for IFN β are expensive and the clinical relevance of the results has been debated. Objective: To establish a cheap, sensitive, and reliable assay for antibodies to 125 I-IFN β, and to correlate levels of antibodies with clinical response to IFN β treatment. Methods: We established a radioimmunoprecipitation assay (RIPA) using 125 I-IFN β. We tested NAB positive sera, healthy control sera, and serial samples of 33 IFN β-1b treated MS patients from the Vancouver cohort of the Berlex pivotal trial who had a high incidence of NABs. Results: We found that the RIPA was highly sensitive for the detection of antibodies to IFN β-1a and -1b, and that there was a strong correlation between reactivity of NAB positive sera for 125 I-IFN β-1b and for 125 I-IFN β-1a. The RIPA was more sensitive and consistent than the NAB. Moreover, there was a trend towards poorer MRI outcomes in RIPA positive patients, but not in NAB-positive patients. Conclusions: The RIPA assay is sensitive and easy to perform. It should be of value in assessing the clinical impact of IFN β antibodies, and its use could help target expensive INF β treatments to those who will respond best.